Limited patient awareness of rheumatoid arthritis (RA) Complications and how to address this - Afzal, Muhammad Zeeshan; Farooq, Fahad; Naveed, Tasmia (Journal of the Pakistan Medical Association, 2026)
To the Editor, We are writing to bring attention to the rising rates of systemic complications of rheumatoid arthritis(RA) and to propose strategies for improved management.Rheumatoid arthritis is often considered a low-priority disease, especially in developing countries, and patients often present late in the course of the disease. This, combined with limited therapeutic options and inconsistent patient follow-up, makes its management even more difficult1 and thus increases the chances of its complications. One of the leading causes of these complications is the lack of awareness among patients, as they mostly consider rheumatoid arthritis to be solely a "joint disease."But rheumatoid arthritis is a systemic disease, and that affects not only joints, but also other tissues and organs including the heart, kidneys, lungs, eyes, skin, and nervous system2. Furthermore, it is not only the disease itself but also its treatment that can lead to long-term complications of which patients may be unaware; for example, long-term use of hydroxychloroquine can cause serious retinal damage.3 The primary approach to tacklingthis is by raising patient awareness and providing education so that patients can understand the link between rheumatoid arthritis and its medications with their systemic complications. This knowledge can help in the prevention or early detection of complications, enabling participation in appropriate screening and monitoring to limit the extent of damage³.The main source of knowledge for the patients is their healthcare team, and there is a need to develop structured educational programmes aimed at increasing patient knowledge about their disease and its course.4 Healthcare professionals should provide ongoing, one-on-one educational sessions to all patients with rheumatoid arthritis, complemented by regular assessment of patient knowledge and needs.5 This is just one aspect of addressing this problem; we must also incorporateother innovative methods to educate the patients, and one such approach is to organise regular rheumatoid awareness camps. At these camps, interactive stations could be set up, with each station representing an organ system commonly affected by the disease. At each station, patients would receive targeted education brief education and basic screening for related complications. Thus, these camps would simultaneously raise patient awareness and provide accessible screening, thereby offering a dual benefit. A coordinated effort on multiple fronts is essential to address rheumatoid arthritis and its complications effectively. Such initiatives could greatly improve patients’ quality of life and ensure that this frequently under-prioritised disease receives the comprehensive management approach it requires.Thank you.